SOLUSI PEMBERANTASAN KORUPSI DI INDONESIA DALAM PERSPEKTIF HISTORIS DAN YURIDIS - Dhimas Rudy Hartanto; Widodo .; Panji Suwarno; Siswo Hadi Sumantri (Jurnal Education and Development, 2021)
The Covid-19 pandemic which has an impact on various sectors of life in Indonesia. In the course of national development, Indonesia is faced with obstacles in the form of the spread of Covid-19 which is increasing every day. Various efforts have been made by the government to maintain the stability of the life of the nation and state. These efforts were blocked again by the existence of criminal acts of corruption amid the problems of the spread of Covid-19 as a national disaster. Corruption that occurred in the midst of a national disaster made Indonesia added to a recession, making Indonesia have to make a new strategy in maintaining the existence of its country. Corruption in the midst of a pandemic raises various views on the threat of punishment. The pro opinion states that perpetrators of criminal acts of corruption can be sentenced to death. However, the contra opinion states that the death penalty should not be imposed because it violates the rights of citizens and human rights. Eradicating corruption can be carried out with a weighted sentence as a deterrent effect. Another alternative can be done by actualizing the values ​​of Pancasila, defending the state, increasing public legal awareness, emphasizing and increasing the system of checks and balances, and collaboration. This method can be a solution in addition to increasing penalties for the perpetrators of corruption in Indonesia.